'Satan in the form of an angel'? The Russian Orthodox Church's controversial case against the Moscow brattsy, 1909 to 1913. Issue 2 (26th May 2020) - Herrlinger, Page
ABSTRACT: This contribution examines the Russian Orthodox Church's controversial case against the popular lay preachers of scripture and sobriety, Ivan Koloskov and Dmitrii Grigor'ev, in the early years of legal religious toleration. Accused of heresy and excommunicated in 1910, the 'Moscow brattsy ' were arrested and tried as 'fanatical and immoral' sectarians. In attempting to prove the brattsy 's alleged deviance to a sceptical public, clergy and missionaries resorted to morally and ethically questionable tactics including false accusations and the fabrication of evidence. While offering a window onto the fraught relations between clergy and laity as Russia entered a modern era of religious pluralism, tenuous democratic practices, and mass media, the case raises issues relevant to the contemporary Russian Orthodox Church, especially its ongoing mission to promote a single community of faith and tradition in a diverse and increasingly 'mediatised' public sphere.